Dataset of numerical modelling results of wave thrust on salt marsh boundaries with different seagrass coverages in a shallow back-barrier estuary - Carmine Donatelli; Neil K. Ganju; Tarandeep Singh Kalra; Sergio Fagherazzi; Nicoletta Leonardi (Data in Brief, 2019)
This article contains data on the effects of seagrass decline on wave energy along the shoreline of Barnegat Bay (USA) previously evaluated in Donatelli et al., 2019. This study was carried out applying the Coupled-Ocean-Atmosphere-Wave-Sediment Transport (COAWST) numerical modelling framework to six historical maps of seagrass distribution. A new routine recently implemented in COAWST was used, which explicitly computes the wave thrust acting on salt marsh boundaries. The numerical modelling results are reported in terms of wind-wave heights for different seagrass coverages, wind speeds and directions. From a comparison with a numerical experiment without submerged aquatic vegetation, we show how the computed wave thrust on marsh boundaries can be reduced by seagrass beds. Keywords: Vegetation, COAWST, Wave thrust